Supporting the Truth and Its Contemporary Applications: In Light of Surah al-Asr - Muhammad Shodiq Ahmad (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2024)
This study aims to explore the concept of